Extrinsic and intrinsic determinants of thermal conductivity in mycelium composites - Wildman, Joni; Shea, Andy; Walker, Pete; Henk, Daniel (Building services engineering research & technology, 2025)
The need for the construction industry to reduce both operational and embodied carbon emissions is urgent. Traditional insulation materials, while effective, require energy-intensive processes and non-renewable resources, making them unsustainable. Mycelium-based composites (MBCs) offer a sustainable alternative with low embodied carbon, biodegradability, and non-toxicity, and studies show promising thermal performance. However, accurate measurement of λ is crucial to ensure effectiveness, requiring an understanding of the factors influencing these measurements. This paper reviews the thermal conductivity of MBCs, covering 19 studies reporting λ values from 0.026 W/mK to 0.18 W/mK. Measurement techniques and their uncertainties are reviewed, as well as additional factors affecting λ, including moisture content, density, temperature, substrate, fungal species, and growth conditions. The influence of the fungal-skin layer and the anisotropic nature of MBCs is discussed. Standardised measurement protocols and thorough methodological reporting are emphasised to ensure comparability. By optimising intrinsic parameters like species-substrate combinations and growth conditions, MBC thermal performance can be improved. This paper informs on MBC thermal characterization, promoting broader adoption in the construction industry and advancing sustainable practices. Consequently, this review aims to guide future research and applications, aiding in reducing both operational and embodied carbon emissions. Practical application The whole-life impact, in energy use or associated carbon emissions, is increasingly used to define building material performance. In addition to operational performance, the constituent materials and associated production processes become very relevant. Consequently, interest in the use of ’would-be’ waste materials and natural building materials with, typically, low embodied carbon has increased significantly. This article aims to provide architects, building services engineers, and others involved in the design, specification, and use of building envelope materials with a state-of-the-art review of the thermal characterisation of bio-composite materials; knowledge of their development and thermal performance will help to inform their use.